Efektivitas Arang Sekam Padi Dalam Menurunkan Kesadahan Air Sumur Gali - Asril, Muh.; Rivai, Abdur; Rasman, Rasman (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
The hardness is one of the chemical parameters in the chemical requirements of clean water. Hardness is a term used of water which contains high amounts of hardness-causing cations. In general, the hardness is caused by the metals or cations with a valence of 2, such as Fe, Sr, Mn, Ca and Mg. The purpose of this study is to determine the effectiveness of rice husk charcoal in reducing the hardness of dug water-wells. The type of this research is True Experimental with a pretest-posttest design. It aims to find out the hardness decrease in dug water-wells before and after the treatment using a combination of variations in thickness and contact time. The results showed the average decrease of water hardness with the variations in the thickness media of rice husk charcoal and contact time. The media thickness of 10 cm with a contact time of 40 minutes, 50 minutes, and 60 minutes are respectively obtained 617,5 mg/l, 463,8 mg/l, and 402 mg/l. As for the media thickness of 20 cm with a contact time of 40 minutes, 50 minutes, and 60 minutes are respectively obtained 434,2 mg/l, 424,7 mg/l, and 312 mg/l. In the media thickness of 30 cm with a contact time of 40 minutes, 50 minutes, and 60 minutes are respectively obtained 208,5 mg/l, 136,4 mg/l, and 120,3 mg/l.As a conclusion, The media thickness of 10 cm with a contact time of  50 minutes is effective in reducing the hardness of dug water-wells. It also fulfills the quality standards allowed by Regulation of Indonesia Health Minister Number. 32 of 2017  which is ≤ 500 mg/l. So that it can be an alternative in reducing the hardness because of easily accessible material. This research can be a consideration for the future researchers in choosing the media of rice husk charcoal. The characteristic of this media is light and easy to float, so that other media are needed as a barrier or ballast in the filtering process and in activation using easily accessible materials.  Keywords : Hardness; Thickness; Contact Time